Comparison of the Catalytic Activity of Mono‐ and Multinuclear Ga Complexes in the ROCOP of Epoxides and Cyclic Anhydrides. Issue 3 (13th December 2021) - Ghosh, Swarup; Glöckler, Eduard; Wölper, Christoph; Linders, Jürgen; Janoszka, Nicole; Gröschel, André H.; Schulz, Stephan
Abstract: Tetranuclear Schiff‐base complexes L 1–3 2 Ga4 ( t ‐Bu)8 1 –3 are highly active and selective (>99 %) catalyst in the alternating ring‐opening copolymerization (ROCOP) of epoxides and anhydrides, yielding polyesters with high molecular weights ( M n ) and narrow dispersity ( Đ ). The thermal properties ( T g ) of the resulting polyester range from 18 °C to 124 °C and increase with increasing steric bulk or rigidity along the polymer backbone. Comparative studies using structurally related complexes L 4 Ga( t ‐Bu)2 4, [L 5 GaR2 ]2 (R= t ‐Bu 5, R=Me 6 ) and L 6 Ga( t ‐Bu)2 7 proved that the Ga2 O2 core of catalyst 1 is the catalytically active species. Abstract : The catalytically active site of tetranuclear Schiff‐base complexes L 1–3 2 Ga4 ( t ‐Bu)8 1 –3, which showed high activity and perfect selectivity (>99 %) in the alternating ROCOP of a series of epoxides and anhydrides to polyesters with high M n and narrow dispersity Đ, was identified.